Ping-pong housing: Women’s post-incarceration trajectories - Smoyer, Amy B; Keene, Danya E; Oyola, M.; Hampton, A (Affilia, 2020)
This study examines the post-incarceration housing experiences of 33 women. Using Residential Timeline Followback methodology, participants were asked to report where they lived at arrest and every location since their release. Follow-up questions asked women to describe these locations, who they lived with, how much they paid, and whether or not they felt safe. Demographic information and criminal justice history were recorded. The data paint a complicated picture of social and community resources, persistence, and struggle. Housing assets lost at incarceration were difficult to recover. Most women bounced between various locations, relying heavily on short-term subsidized congregate housing programs and rarely securing independent housing. Participants described the family, friends, and acquaintances who housed them during reentry as overextended and vulnerable. Implications for policy and practice are explored. © The Author(s) 2020.
Keywords: dept.swk; peer-reviewed

Trusted residents and housing assistance to decrease violence exposure in New Haven (TRUE HAVEN): a strengths-based and community-driven stepped-wedge intervention to reduce gun violence - Tong, Guangyu; Spell, Virginia T.; Horton, Nadine; Thornhill, Thomas; Keene, Danya; Montgomery, Christine; Spiegelman, Donna; Wang, Emily A.; Roy, Brita (BMC Public Health, 2023)
We describe the rationale and study design for “TRUsted rEsidents and Housing Assistance to decrease Violence Exposure in New Haven (TRUE HAVEN),” a prospective type 1 hybrid effectiveness/implementation study of a multi-level intervention using a stepped wedge design. TRUE HAVEN aims to lower rates of community gun violence by fostering the stability, wealth, and well-being of individuals and families directly impacted by incarceration through the provision of stable housing and by breaking the cycle of trauma.
Keywords: Collective wellbeing; Community-based intervention; Gun violence; Housing stability; Incarcerated population; Learn as you go; Multi-component implementation; Stepped wedge design; Structural racism; dept.swk; peer-reviewed